Serotype 3 Remains the Leading Cause of Invasive Pneumococcal Disease in Adults in Portugal (2012–2014) Despite Continued Reductions in Other 13-Valent Conjugate Vaccine Serotypes - Horácio, Andreia N.; Silva-Costa, Catarina; Lopes, Joana P.; Ramirez, Mário; Melo-Cristino, José; , Portuguese Group for the Study of Streptococcal Infections; Vaz, Teresa; Gião, Marília; Ferreira, Rui; Fonseca, Ana Buschy; Oliveira, Henrique; Silva, Ana Cristina; et al. (Frontiers in Microbiology, 2016)
Since 2010 the 13-valent pneumococcal conjugate vaccine (PCV13) replaced the 7-valent vaccine (PCV7) as the leading pneumococcal vaccine used in children through the private sector. Although neither of the PCVs were used significantly in adults, changes in adult invasive pneumococcal disease (IPD) were expected due to herd protection. We characterized n=1163 isolates recovered from IPD in adults in 2012-2014 with the goal of documenting possible changes in serotype prevalence and antimicrobial resistance. Among the 54 different serotypes detected, the most frequent, accounting for half of all IPD, were serotypes: 3 (14%), 8 (11%), 19A (7%), 22F (7%), 14 (6%) and 7F (5%). The proportion of IPD caused by PCV7 serotypes remained stable during the study period (14%), but was smaller than in the previous period (19% in 2009-2011, p=0.003). The proportion of IPD caused by PCV13 serotypes decreased from 51% in 2012 to 38% in 2014 (p<0.001), mainly due to decreases in serotypes 7F and 19A. However, PCV13 serotype 3 remained relatively stable and the most frequent cause of adult IPD. Non-PCV13 serotypes continued the increase initiated in the late post-PCV7 period, with serotypes 8 and 22F being the most important emerging serotypes. Serotype 15A increased in 2012-2014 (0.7% to 3.5%, p=0.011) and was strongly associated with antimicrobial resistance. However, the decreases in resistant isolates among serotypes 14 and 19A led to an overall decrease in penicillin non-susceptibility (from 17% to 13%, p=0.174) and erythromycin resistance (from 19% to 13%, p=0.034). Introduction of PCV13 in the NIP for children, as well as its availability for adults may further alter the serotypes causing IPD in adults in Portugal and lead to changes in the proportion of resistant isolates.